Saidal Masfiyuddin: Childhood Life Before Becoming a Member of the West Sumatra Provincial Parliament 2002-2019 - Oktavianus, Satria; Herwandi, Herwandi; Nopriyasman, Nopriyasman (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research aims to understand Saidal Masfiyuddin's youth or childhood. These childhood conditions will shape Saidal Masfiyuddin's character in the future. Until this character turned into capital for him as a politician until he became a Member of the South Pesisir Regency DPRD and a Member of the West Sumatra Province DPRD. This research was conducted using 4 stages of historical research. The first is heuristic, namely the collection stage in the form of books, articles, etc. The second source criticism is testing the data by carrying out internal and external criticism of the authenticity of the data obtained. The third interpretation is the interpretation of data so that it becomes meaningful facts. The final stage is writing history in the form of a thesis. The research results show that Nagari Surantih as Saidal's birthplace influenced his political attitudes in the future. Saidal was a smart student during school despite his limitations. These limitations made Saidal finally found CV. Mandala Karya was a stepping stone to join the Golkar party and a career as a legislative member.